Developments in the use of tyrosine kinase inhibitors in the treatment of renal cell carcinoma. Issue 3 (4th March 2019) - Reed, Jarred P.; Posadas, Edwin M.; Figlin, Robert A.
ABSTRACT: Introduction : Renal cell carcinoma (RCC) is among the most commonly diagnosed solid malignancies, but until recently there were few systemic treatment options for advanced disease. Since 2005, the treatment landscape has been transformed by the development of several novel systemic therapies. In particular, tyrosine kinase inhibitors (TKIs) targeting the vascular endothelial growth factor (VEGF) pathway have been instrumental in improving outcomes in patients with metastatic disease. Areas covered : The armamentarium of TKIs available for the treatment of RCC has expanded in recent years. The most active area of research at this time is the development of treatment regimens combining newer-generation TKIs and immune checkpoint inhibitors. Emerging data point to a role for combination therapy in the frontline management of advanced RCC. Other ongoing areas of research include the use of TKIs in the adjuvant setting and the role of cytoreductive nephrectomy within a changing treatment landscape. Expert opinion : Although TKIs and immune checkpoint inhibitors have incrementally improved outcomes for patients with advanced RCC, long-term survival remains poor. The development of regimens combining these agents represents the next step in the evolution of the field. For the clinician, this will offer exciting possibilities and novel challenges. Trial registration: ClinicalTrials.gov identifier: NCT02493751. Trial registration: ClinicalTrials.gov identifier: NCT02133742. Trial registration: ClinicalTrials.gov identifier: NCT02501096. Trial registration: ClinicalTrials.gov identifier: NCT02496208. Trial registration: ClinicalTrials.gov identifier: NCT02684006. Trial registration: ClinicalTrials.gov identifier: NCT02853331. Trial registration: ClinicalTrials.gov identifier: NCT02811861. Trial registration: ClinicalTrials.gov identifier: NCT03141177.